Clinical practice guidelines for recurrent miscarriage in high-income countries: a systematic review. Issue 6 (June 2021) - Hennessy, Marita; Dennehy, Rebecca; Meaney, Sarah; Linehan, Laura; Devane, Declan; Rice, Rachel; O'Donoghue, Keelin
Abstract: Recurrent miscarriage affects 1–2% of women of reproductive age, depending on the definition used. A systematic review was conducted to identify, appraise and describe clinical practice guidelines (CPG) published since 2000 for the investigation, management, and/or follow-up of recurrent miscarriage within high-income countries. Six major databases, eight guideline repositories and the websites of 11 professional organizations were searched to identify potentially eligible studies. The quality of eligible CPG was assessed using the Appraisal of Guidelines for Research and Evaluation (AGREE II) Tool. A narrative synthesis was conducted to describe, compare and contrast the CPG and recommendations therein. Thirty-two CPG were included, from which 373 recommendations concerning first-trimester recurrent miscarriage were identified across four sub-categories: structure of care (42 recommendations, nine CPG), investigations (134 recommendations, 23 CPG), treatment (153 recommendations, 24 CPG), and counselling and supportive care (46 recommendations, nine CPG). Most CPG scored 'poor' on applicability (84%) and editorial independence (69%); and to a lesser extent stakeholder involvement (38%) and rigour of development (31%). Varying levels of consensus were found across CPG, with some conflicting recommendations. Greater efforts are required to improve the quality of evidence underpinning CPG, the rigour of their development and the inclusion of multi-disciplinary perspectives, including those with lived experience of recurrent miscarriage.